Formulasi Kebijakan Tata Kelola Perusahaan Yang Baik Bagi Badan Usaha Milik Daerah Dalam Rangka Mitigasi Masalah Hukum - Dwi Alfianto; Ali Rido (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Implementing the principles of good corporate governance is a necessity for Regionally Owned Enterprises. However, this is often overlooked so that many Regional Owned Enterprises are not anticipatory in facing legal problems. Through this article, a formulation for preventing legal problems is offered which includes: 1). Preparation of document and enforcement of a code of ethics; 2). Whistle blowing system guidelines; 3). Anti-Corruption, Collusion and Nepotism guidelines; and 4). Guidelines for public information disclosure. Through these guidelines, it is hoped that the existence of Regional Owned Enterprises can provide benefits to the general public or local communities, regional economic development, and the existence of Regional Owned Enterprises must be based on regional needs and feasibility.